2011
DOI: 10.1063/1.3553884
|View full text |Cite
|
Sign up to set email alerts
|

Structural templating and growth behavior of copper phthalocyanine thin films deposited on a polycrystalline perylenetetracarboxylic dianhydride layer

Abstract: Interdependence between stress, preferred orientation, and surface morphology of nanocrystalline TiN thin films deposited by dual ion beam sputtering Growth kinetics, structure, and morphology of para-quaterphenyl thin films on gold (111)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…It is concluded that the flat-on structure of H2TTDPz act as a template for formation of the thin-film structure of CuPc. This is similar to the templating effects of PTCDA [6,21,22] and of hydrogen-terminated Si(111) [19], for the CuPc thin films. It is further notable that the flat-on structure of CuPc is maintained up to a film thickness of 60 nm, though the XRD of this film (Fig.…”
Section: Resultssupporting
confidence: 61%
“…It is concluded that the flat-on structure of H2TTDPz act as a template for formation of the thin-film structure of CuPc. This is similar to the templating effects of PTCDA [6,21,22] and of hydrogen-terminated Si(111) [19], for the CuPc thin films. It is further notable that the flat-on structure of CuPc is maintained up to a film thickness of 60 nm, though the XRD of this film (Fig.…”
Section: Resultssupporting
confidence: 61%
“…6,7 So, understanding the growth dynamics of organic thin films is one of the key issues in the field of organic electronics. In case of heterostructures, such as organic-organic heterostructures 8,9 (for organic diode) and organic-inorganic heterostructures 10 (for electrode/contacts), the knowledge of growth kinetics is of utmost importance, since their interfacial structures can play a crucial role on the scaling properties. However, there has been no report on the scaling behavior and growth dynamics of SnCl 2 Pc on different substrates that are most relevant for device applications.…”
mentioning
confidence: 99%
“…Previously, several studies have identified substrates that have the proper molecule–substrate interactions to induce this “lying-down” morphology for thick, oriented films of polyacenes, perylene-derivatives, and phthalocyanines. The substrates include graphite (highly ordered pyrolitic graphite, HOPG), MoS 2 , copper iodide, alkali metal halides, and even other organic molecules such as perylene-3,4,9,10-tetracarboxylic-3,4,9,10-dianhydride (PTCDA) and pentacene . One problem, however, is that the integration of films grown on these templates into optoelectronic devices has proven to be challenging because these templates are either partially or completely opaque or poorly conducting.…”
mentioning
confidence: 99%